Inertial and aerodynamic tuning of passive devices for load alleviation on wind turbines. Issue 10 (September 2016) - Croce, A; Gualdoni, F; Montinari, P; Riboldi, C E D; Bottasso, C L
Abstract: This paper describes tuning concepts for passive devices aimed at load alleviation in wind turbines. Two types of tuning are considered: inertial and aerodynamic. The first concept is illustrated with reference to a passive flap, while the second with reference to a passive tip. In both cases, the goal is to reduce loads with devices that are as simple as possible, and do not require sensors nor actuators. The main features and critical issues of each concept are highlighted and illustrated with reference to a large conceptual 10 MW wind turbine.